State-owned enterprises and cluster-based industrialization: Evidence from Bangladesh - Monzur Hossain (Asian Development Bank Institute (ADBI), 2019)
This paper assesses the role of the Bangladesh Small and Cottage Industries Corporation (BSCIC) in the cluster-based development of SMEs over time using firm-level survey data, as well as critically examining the institutional impact on the industrialization process in Bangladesh. The role of BSCIC estates in industrialization is assessed mainly through several factors: (i) industrial output; (ii) employment; (iii) technological acquisition; and (iv) contribution to the tertiary economy. Analysis suggests that BSCIC contributes to 12.4% of total SME manufacturing firms, 21% of total SME employment, and 18.7% of total manufacturing production indicating relatively better performance of BSCIC estates/clusters. The results show that despite being associated with negative practices such as bureaucratic inefficiencies and corruption in estate management, the role of BSCIC as a state-owned enterprise (SOE) in promoting industrialization is largely positive. New entry and specialization are observed, though the rate is very low. On the other hand, estates established in the most recent phases of development have accumulated a more technology-intense production process leading to higher labor productivity. This paper highlights the necessity of reform in BSCIC's estate management in order to better utilize plots as well as to bring efficiencies in their activities to achieve the intended objective of industrialization.
Keywords: L6; O2; 330; state-owned enterprises; BSCIC; industrial zones; Bangladesh